2021
DOI: 10.3389/fmars.2020.496688
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Habitat-Forming, Deep-Sea Sponges in the Barents Sea: The Value of Data

Abstract: The use of species occurrence as a proxy for habitat type is widespread, probably because it allows the use of species distribution modeling (SDM) to cost-effectively map the distribution of e.g., vulnerable marine ecosystems. We have modeled the distribution of epibenthic megafaunal taxa typical of soft-bottom, Deep-Sea Sponge Aggregations (DSSAs), i.e., “indicators,” to discover where in the Barents Sea region this habitat is likely to occur. The following taxa were collectively modeled: Hexadella cf. dedrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Moreover, in models constructed with the inclusion of depth (63 shallow-water species; 12 deep-sea species; see Appendix S1 Table S1.3), depth was recovered as most relevant for both groups, followed by temperature and salinity. This aligns well with the findings of other studies (e.g., Pearman et al, 2020;Gonzalez-Mirelis et al 2021), which have indicated that depth along with temperature and salinity are relevant for defining benthic species distributions. It is relevant to note that, previous studies have highlighted the relevance of oxygenation, pH and food supply (or POC flux) in the maintenance of the ecosystem functioning (Sweetman et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in models constructed with the inclusion of depth (63 shallow-water species; 12 deep-sea species; see Appendix S1 Table S1.3), depth was recovered as most relevant for both groups, followed by temperature and salinity. This aligns well with the findings of other studies (e.g., Pearman et al, 2020;Gonzalez-Mirelis et al 2021), which have indicated that depth along with temperature and salinity are relevant for defining benthic species distributions. It is relevant to note that, previous studies have highlighted the relevance of oxygenation, pH and food supply (or POC flux) in the maintenance of the ecosystem functioning (Sweetman et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Using biological abundance data, rather than presence/absence data, retains information about abundances within spatiallyexplicit segments observed in this study. This makes the community-environment relationship model more sensitive to variation among communities (Cushman and McGarigal, 2004) which was recently exemplified in a study that compared the usefulness of presence/absence and species abundance data for determination of areas that may require management attention (Gonzalez-Mirelis et al, 2021). They found presence/absence to be insufficient for applied management as modeled presence/absence data highlighted areas that were either too large or too small for their purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, many studies obtain presence/absence data either to establish a species inventory or due to the difficulties in obtaining accurate counts of organisms per unit area (Hargrave et al, 2004;Mortensen and Buhl-Mortensen, 2005), which limits the usefulness of the data for detecting areas of high abundances or biodiversity for management applications (Gonzalez-Mirelis et al, 2021). Using species abundance data can provide a more comprehensive representation of benthic communities that can be used to improve models designed to understand species distribution patterns under a changing climate (Morato et al, 2020) or improve species distribution models.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent maps [11] incorporate near-bottom oceanographic predictor variables (temperature, salinity, currents), and highlight how important such variables are in shaping biotope distribution. Similarly, early MAREANO models of vulnerable biotopes [12], a sister product to the general biotope maps, did not use oceanographic data but later updates have benefitted considerably from their inclusion [13].…”
Section: Introductionmentioning
confidence: 99%